The Effectiveness Of Charismatic Movements In Fostering New Evangelization: Case Of Vincentian Ministries In The Archdiocese Of Nairobi, Kenya - Wambugu, James (Advances in Social Sciences Research Journal, 2018)
The study examines the effectiveness of charismatic movements (CMs) in fostering new evangelization: Case of the Vincentian Ministry (VM) in the Archdiocese of Nairobi, Kenya. The study focused on the research questions: How is VM an agent of evangelization? The research used the Market Choice Theory that emphasizes that conversion or recruitment is not something that merely happens to an individual. Rather it is something that the individual can deliberately achieve. We predominantly employedconvergent mixed method research designusing both quantitative and qualitative research approach. This entailed collection of primary data from a sample of 266 respondents selected through probability and non-probability sampling techniques. The findings revealed that the VM demonstrated solid or grounded treatment of the Scripture, pastoral care, catechetical instructions and witnessing. In conclusion, the study recommends dialogue with the local hierarchy, review of seminary curriculum to incorporate compulsory subject on the CMs, gifts, and charisms of the Spirit to bring dynamism in evangelization. The laity should be equally empowered through training in theology, philosophy, management and administration to promote meaningful collaboration with the ordained ministers in evangelization.